The effect of environmental costs, carbon emission disclosure, and GCG on tax avoidance - Krista Putra Patarianno; Sufiyati Sufiyati (Educoretax, 2026)
Tax avoidance is one of the strategies commonly employed by companies to legally minimize their tax burden. At the same time, increasing demands for social and environmental responsibility have encouraged companies to pay greater attention to environmental costs, carbon emission disclosure, and the implementation of good corporate governance in their operations. This study aims to examine the effect of environmental costs, carbon emission disclosure, and good corporate governance on tax avoidance in energy sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. The research employed a quantitative approach using secondary data obtained from financial statements, annual reports, and sustainability reports. The sample was selected using purposive sampling with a total of 85 observations. Data were analyzed using panel data regression with EViews 14, and the Random Effect Model (REM) was selected as the most appropriate model. The results indicate that environmental costs have a significant negative effect on tax avoidance. Meanwhile, carbon emission disclosure and good corporate governance have no significant effect on tax avoidance. These findings suggest that higher environmental costs reflect a company's commitment to social and environmental responsibility, thereby reducing tax avoidance practices, while carbon emission disclosure and good corporate governance have not become determining factors in tax avoidance policies among energy sector companies.